Foreign Operations of Swedish Manufacturing Firms - Evidence from the IUI Survey on Multinationals 2003 - Katariina Hakkala; David Zimmermann (The Research Institute of Industrial Economics (IUI), 2005)
The paper serves as a documentation of the survey IUI has conducted on Swedish multinational firms (MNEs) in 2004. It describes recent trends in the operations of Swedish multinational firms participating in the survey and foreign direct investment (FDI) of Swedish firms in general. The survey is a follow-up of the surveys made by IUI since 1970s. The database covers information about the Swedish part of manufacturing multinational firms and the foreign affiliates of the firms. The following years are covered: 1965, 1970, 1974, 1978, 1986, 1990, 1994, 1998 and 2003.
Keywords: F21; F23; 330; Multinational Enterprises; Foreign Direct Investment; Spillovers; Research and Development; Verarbeitendes Gewerbe; Multinationales Unternehmen; Direktinvestition; Schwedisch